Health Assessment of Buksa Tribe: Exploring CSR Models for Indigenous Community Empowerment in Ramnagar Block, Nainital District - Kalra, Mohit; Nautiyal, Arpan; Singh, Krishnapal (The Scientific Temper, 2025)
The Buksa tribe, an Indigenous people living in Uttarakhand, India, faces various health and wellness problems. This research examines how long someone from Buksa live, considering the plethora of socio-economic factors that contributed to the situation in which they find themselves. The study employed a mixed-methods design, involving qualitative interviews and quantitative data analysis, to comprehensively analyse key determinants of life expectancy among the people of Buksa. The way their health is affected by limited access to healthcare services and traditional practices is explored in detail. This study also looks into how these healthcare disparities should be addressed by CSR (Corporate Social Responsibility) programs and sustainable business partnerships. It highlights how social entrepreneurship models could enhance healthcare access while upholding customs and encouraging community empowerment. The findings reflect, there are chances for companies to adopt sustainable development plans that support SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). These practices ultimately improve the health outcomes of Indigenous communities while generating value that benefits both businesses and underserved communities.